Corrosion-resistant refractory material and preparation method thereof
By modifying the preparation method of PP fiber, the corrosion resistance and compressive strength of bauxite refractories have been improved, solving the problems of insufficient refractoriness and flame retardancy of existing materials, and enabling wider application.
Patent Information
- Application Number
- CN202511670671.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2025-12-12
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing refractory materials made from bauxite have poor corrosion resistance and compressive strength. The use of PP fiber in refractory materials is limited, and its high-temperature resistance and flame retardancy are insufficient.
Modified PP fibers are used, which are modified by silane coupling agent to modify pyrophyllite powder, grafted with sodium sulfonate and benzimidazole, to form modified PP fibers containing sodium sulfonate groups and polybenzimidazole structures, thereby improving their high temperature resistance and flame retardancy, and improving their compatibility with raw materials such as bauxite and metakaolin to form a dense protective carbon layer.
It improves the corrosion resistance, compressive strength, and refractoriness of refractory materials, and expands their application range.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of refractory materials, and particularly relates to a corrosion-resistant refractory material and a preparation method thereof. BACKGROUND
[0002] Refractory materials are widely used in the fields of steel, non-ferrous metals, glass, cement, ceramics, petrochemicals, machinery, boilers, light industry, electric power and military industry, and are essential basic materials for ensuring the production operation and technological development of these industries.
[0003] Bauxite is widely used in refractory materials due to its excellent high-temperature resistance, thermal conductivity, wear resistance and cold-thermal shock resistance. However, the corrosion resistance and compressive strength of the refractory material prepared from bauxite are not satisfactory. In the past, fibers such as pp fibers were used to form a network-like attachment framework to maintain the overall performance of the refractory material, thereby improving the overall strength, impact resistance and service life of the refractory material. However, the high-temperature resistance of pp fibers is poor, and they do not have flame retardant properties, which limits their use in refractory materials.
[0004] Therefore, a suitable modification method is needed to improve the high-temperature resistance and flame retardant properties of pp fibers and apply them to refractory materials, while improving the corrosion resistance of bauxite refractory materials, so as to obtain bauxite refractory materials with excellent refractoriness, corrosion resistance and compressive strength, and expand their application range. SUMMARY
[0005] To solve the above technical problems, the present application provides a corrosion-resistant refractory material and a preparation method thereof.
[0006] The object of the present application can be achieved by the following technical solutions: A corrosion-resistant refractory material, comprising the following raw materials by weight: 70-80 parts of bauxite clinker, 15-25 parts of metakaolin, 10-15 parts of aluminum ash, 10-12 parts of corundum, 5-7 parts of phenolic resin and 12-14 parts of modified pp fiber; Further, the fineness of the metakaolin is 400-800 mesh, and the corundum is 400-800 mesh powder; The preparation of the corrosion-resistant refractory material comprises the following steps: mixing and stirring the bauxite clinker, metakaolin, aluminum ash, corundum, phenolic resin and modified pp fiber for 1-1.5 h, aging, pressing into shape, drying at 200-300 DEG C for 4-5 h, and then sintering at 1300-1600 DEG C for 15-16 h to obtain the corrosion-resistant refractory material.
[0007] The preparation of the modified pp fiber comprises the following steps: Step A1: Mix silane coupling agent and ethanol and stir for 2-3 hours to obtain solution (1); grind pyrophyllite, measure particle size, and keep it in an oven at 110-120℃ for 30-40 minutes to obtain pyrophyllite powder. Take out the pyrophyllite powder and add anhydrous ethanol and stir for 2-2.5 hours. Then add solution (1) at 40-45℃ and continue stirring for 6-7 hours. Keep it in an oven at 120-125℃ for 6-7 hours to obtain modified pyrophyllite. Furthermore, the silane coupling agent is 5-hexenyltriethoxysilane, the volume fraction of ethanol is 95%, and the ratio of silane coupling agent to ethanol is 0.8-1.5g:20-23mL; pyrophyllite is ground using a planetary ball mill at a speed of 300-400rpm and a ball-to-material ratio of 18-20:1 for 1.5-1.7h; after grinding, the average particle size of pyrophyllite is measured to be 900-950nm by a particle size analyzer, and the ratio of pyrophyllite powder, anhydrous ethanol, and solution (1) is 50-52g:110-120mL:25-27mL; In step A1, the surface of pyrophyllite powder is modified using a silane coupling agent to obtain modified pyrophyllite with carbon-carbon double bonds on the surface. Step A2: Modified pyrophyllite, sodium dihydrate of 2-mercaptobenzimidazole-5-sulfonate, DMF, and 4-dimethylaminopyridine are stirred under ultraviolet light for 30-40 minutes and then dried to obtain product 1. Furthermore, the ratio of modified pyrophyllite, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, DMF, and 4-dimethylaminopyridine is 6-8g:0.13-0.17g:30-40mL:0.02-0.03g, the power of the ultraviolet light is 100-150W, the wavelength is 365nm, and the irradiation distance is 18-20cm; During step A2, the carbon-carbon double bonds on the surface of the modified pyrophyllite undergo a click reaction with the mercapto group of sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate to obtain product 1, which contains sodium sulfonate group, benzimidazole and other grafted pyrophyllite. Step A3: Add 5-hexenoic acid to DMF, add sulfoxide under stirring, and reflux and stir at 45-55℃ for 5-6 hours to obtain acyl chloride; mix product 1, potassium carbonate and sulfoxide to obtain a mixture (1), then add acyl chloride to sulfoxide and stir to obtain a mixture (2); in an ice-water bath, add mixture (2) dropwise to mixture (1), then heat to 45-50℃ and stir for 9-10 hours to obtain monomer; Furthermore, the ratio of 5-hexenoic acid, DMF, and dimethyl sulfoxide is 12-13g: 90-100mL: 18-20g; the ratio of product 1, potassium carbonate, and dimethyl sulfoxide in mixture (1) is 3-4g: 0.6-0.7g: 15-20mL; the ratio of acyl chloride and dimethyl sulfoxide in mixture (2) is 14-15g: 35-45mL; and the ratio of mixture (1) to mixture (2) is 30-40mL: 7-9mL. In step A3, 5-hexenoic acid reacts with thionyl chloride to obtain acyl chloride; the acyl chloride then reacts with the secondary amine in benzimidazole in product 1 to obtain a monomer containing a terminal carbon-carbon double bond. Step A4: In a protective gas atmosphere, add the monomer and crosslinking agent to toluene, stir for 15-20 minutes, then add PP fiber and continue stirring for another 15-20 minutes. Seal and then... 60 After irradiating with Co γ rays for 10-11 hours, the product was removed, rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified PP fibers. Furthermore, the ratio of toluene, monomer, crosslinking agent, and PP fiber is 400-450mL: 38-40g: 13-15g: 108-110g, and the crosslinking agent is divinylbenzene; 60 The dose rate of Co-γ irradiation is 3-5 kGy / h; During the reaction in step A4, 60 Under the influence of Coγ-ray irradiation and crosslinking agent, monomers are grafted onto PP fibers to obtain modified PP fibers; The beneficial effects of this invention are as follows: This invention discloses a corrosion-resistant refractory material comprising raw materials such as bauxite clinker, metakaolin, aluminum ash, corundum, phenolic resin, and modified PP fiber. The modified PP fiber is obtained by grafting PP fiber with monomers containing sodium sulfonate, benzimidazole, and nano-sized pyrophyllite powder. After modification, the nano-sized pyrophyllite not only improves the mechanical strength of the PP fiber itself, thereby enhancing the mechanical strength of the refractory material, but also enhances the corrosion resistance of the refractory material due to the excellent corrosion resistance of pyrophyllite. Grafting sodium sulfonate with PP fiber improves the compatibility of PP fiber with raw materials such as bauxite clinker, metakaolin, aluminum ash, and corundum, resulting in a more uniformly mixed refractory material. Furthermore, the sulfur element in the sodium sulfonate group generates non-combustible gases such as sulfur dioxide during combustion, diluting the concentration of combustible gases. It is also solidified in the carbon layer in the form of sodium sulfate and sodium sulfite compounds, forming a dense and thick protective carbon layer, reducing heat at the combustion site. The modified PP fiber exhibits excellent flame retardancy by effectively preventing further combustion of the PP fiber and suppressing smoke release. Grafting the modified monomer containing benzimidazole onto the PP fiber not only forms a polybenzimidazole structure (which possesses excellent high-temperature resistance, thus improving the high-temperature resistance of the modified PP fiber and making it more suitable for use in refractory materials, thus enhancing the refractoriness of the refractory material), but also generates a large amount of nitrogen, which, during combustion, forms non-combustible gas to dilute combustible gas, synergistically improving the flame retardancy of the modified PP fiber with sodium sulfonate. Furthermore, the grafting of sodium sulfonate also improves the solubility of polybenzimidazole.
[0008] After the mechanical strength, flame retardancy and high temperature resistance of modified PP fiber are improved, it will be more beneficial to the improvement of the compressive strength and refractoriness of refractory materials. Therefore, the refractory material of the present invention has excellent corrosion resistance, compressive strength and refractoriness, and is worth promoting and using. Detailed Implementation
[0009] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example
[0010] A modified PP fiber, the preparation of which includes the following steps: Step A1: Mix 5-hexenyltriethoxysilane and ethanol and stir for 2 hours to obtain solution (1); grind pyrophyllite (supplier: Lingshou County Pengxia Furnace Lining Material Processing Plant), measure particle size, and keep warm in an oven at 110℃ for 30 minutes to obtain pyrophyllite powder. Take out the pyrophyllite powder and add anhydrous ethanol and stir for 2 hours. Then add solution (1) at 40℃ and continue stirring for 6 hours. Keep warm in an oven at 120℃ for 6 hours to obtain modified pyrophyllite; the volume fraction of ethanol is 95%, and the ratio of 5-hexenyltriethoxysilane to ethanol is 0.8g:20mL; pyrophyllite is ground using a planetary ball mill (supplier: Shicheng County Haoxin Mining Machinery Manufacturing Plant, model: XQM-0.4) at a speed of 300rpm and a ball-to-material ratio of 18:1 for 1.5 hours; after grinding, the pyrophyllite is tested with a particle size analyzer (Malvin Zetasizer Nano). The average particle size of ZS type was 950 nm. The ratio of pyrophyllite powder, anhydrous ethanol and solution (1) was 50 g: 110 mL: 25 mL. Step A2: Modified pyrophyllite, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, DMF, and 4-dimethylaminopyridine were stirred under ultraviolet light for 30 min and dried to obtain product 1. The ratio of modified pyrophyllite, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, DMF, and 4-dimethylaminopyridine was 6 g: 0.13 g: 30 mL: 0.02 g, and the ultraviolet light power was 150 W, the wavelength was 365 nm, and the irradiation distance was 18 cm. Step A3: Add 5-hexenoic acid to DMF, add sulfoxide under stirring, and reflux at 45°C for 5 hours to obtain acyl chloride; mix product 1, potassium carbonate and sulfoxide to obtain mixture (1), then add acyl chloride to sulfoxide and stir to obtain mixture (2); in an ice-water bath, add mixture (2) dropwise to mixture (1), then heat to 45°C and stir for 9 hours to obtain monomer; the ratio of 5-hexenoic acid, DMF and sulfoxide is 12g:90mL:18g; the ratio of product 1, potassium carbonate and sulfoxide in mixture (1) is 3g:0.6g:15mL; the ratio of acyl chloride and sulfoxide in mixture (2) is 14g:35mL; the ratio of mixture (1) to mixture (2) is 30mL:7mL. Step A4: In a nitrogen atmosphere, add the monomer and crosslinking agent to toluene, stir for 15 minutes, then add PP fiber (supplier: Taian Songze Composite Materials Co., Ltd.), continue stirring for another 15 minutes, seal, and then... 60 After irradiating with Co γ rays for 10 hours, the product was removed, rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified PP fiber. The ratio of toluene, monomer, crosslinking agent, and PP fiber was 400mL:38g:13g:108g, and the crosslinking agent was divinylbenzene. 60The dose rate of Co-γ irradiation was 3 kGy / h. Example
[0011] A modified PP fiber, the preparation of which includes the following steps: Step A1: Mix 5-hexenyltriethoxysilane and ethanol and stir for 2.5 h to obtain solution (1); grind pyrophyllite (supplier: Lingshou County Pengxia Furnace Lining Material Processing Plant), measure particle size, and keep warm in an oven at 115℃ for 35 min to obtain pyrophyllite powder. Take out the pyrophyllite powder and add anhydrous ethanol and stir for 2.3 h. Then add solution (1) at 42℃ and continue stirring for 6.5 h. Keep warm in an oven at 120℃ for 6.5 h to obtain modified pyrophyllite; the volume fraction of ethanol is 95%, and the ratio of 5-hexenyltriethoxysilane to ethanol is 1.1 g: 21 mL; grind pyrophyllite using a planetary ball mill (supplier: Shicheng County Haoxin Mining Machinery Manufacturing Plant, model: XQM-0.4) at a speed of 350 rpm and a ball-to-material ratio of 19:1 for 1.6 h; after grinding, use a particle size analyzer (Malvin Zetasizer Nano) to measure particle size. The average particle size of ZS type was 950 nm. The ratio of pyrophyllite powder, anhydrous ethanol and solution (1) was 51 g: 115 mL: 26 mL. Step A2: Modified pyrophyllite, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, DMF, and 4-dimethylaminopyridine were stirred under ultraviolet light for 35 min and dried to obtain product 1. The ratio of modified pyrophyllite, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, DMF, and 4-dimethylaminopyridine was 7 g: 0.15 g: 35 mL: 0.025 g. The ultraviolet light power was 150 W, the wavelength was 365 nm, and the irradiation distance was 19 cm. Step A3: Add 5-hexenoic acid to DMF, add sulfoxide under stirring, and reflux at 50°C for 5.5 h to obtain acyl chloride; mix product 1, potassium carbonate and sulfoxide to obtain mixture (1), then add acyl chloride to sulfoxide and stir to obtain mixture (2); in an ice-water bath, add mixture (2) dropwise to mixture (1), then heat to 47°C and stir for 9.5 h to obtain monomer; the ratio of 5-hexenoic acid, DMF and sulfoxide is 12.5 g: 95 mL: 19 g; the ratio of product 1, potassium carbonate and sulfoxide in mixture (1) is 3.5 g: 0.65 g: 17 mL; the ratio of acyl chloride and sulfoxide in mixture (2) is 14.5 g: 40 mL; the ratio of mixture (1) to mixture (2) is 35 mL: 8 mL; Step A4: In a nitrogen atmosphere, add the monomer and crosslinking agent to toluene, stir for 17 minutes, then add PP fiber (supplier: Taian Songze Composite Materials Co., Ltd.), continue stirring for another 17 minutes, seal, and then...60 After irradiating with Co γ rays for 10.5 h, the modified PP fiber was obtained by rinsing with anhydrous ethanol, extracting with acetone, and drying. The ratio of toluene, monomer, crosslinking agent and PP fiber was 420 mL: 39 g: 14 g: 109 g, and the crosslinking agent was divinylbenzene. 60 The dose rate of Co-γ irradiation was 4 kGy / h. Example
[0012] A modified PP fiber, the preparation of which includes the following steps: Step A1: Mix 5-hexenyltriethoxysilane and ethanol and stir for 3 hours to obtain solution (1); grind pyrophyllite (supplier: Lingshou County Pengxia Furnace Lining Material Processing Plant), measure particle size, and keep warm in a 120℃ oven for 40 minutes to obtain pyrophyllite powder. Take out the pyrophyllite powder and add anhydrous ethanol and stir for 2.5 hours. Then add solution (1) at 45℃ and continue stirring for 7 hours. Keep warm in a 125℃ oven for 7 hours to obtain modified pyrophyllite; the volume fraction of ethanol is 95%, and the ratio of 5-hexenyltriethoxysilane to ethanol is 1.5g:23mL; pyrophyllite is ground using a planetary ball mill (supplier: Shicheng County Haoxin Mining Machinery Manufacturing Plant, model: XQM-0.4) at a speed of 400rpm and a ball-to-material ratio of 20:1 for 1.7 hours; after grinding, the pyrophyllite is tested with a particle size analyzer (Malvin Zetasizer Nano). The average particle size of ZS type was 950 nm. The ratio of pyrophyllite powder, anhydrous ethanol and solution (1) was 52 g: 120 mL: 27 mL. Step A2: Modified pyrophyllite, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, DMF, and 4-dimethylaminopyridine were stirred under ultraviolet light for 40 min and dried to obtain product 1. The ratio of modified pyrophyllite, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, DMF, and 4-dimethylaminopyridine was 8 g: 0.17 g: 40 mL: 0.03 g, and the ultraviolet light power was 150 W, the wavelength was 365 nm, and the irradiation distance was 20 cm. Step A3: Add 5-hexenoic acid to DMF, add sulfoxide under stirring, and reflux at 55°C for 6 hours to obtain acyl chloride; mix product 1, potassium carbonate and sulfoxide to obtain mixture (1), then add acyl chloride to sulfoxide and stir to obtain mixture (2); in an ice-water bath, add mixture (2) dropwise to mixture (1), then heat to 50°C and stir for 10 hours to obtain monomer; the ratio of 5-hexenoic acid, DMF and sulfoxide is 13g:100mL:20g; the ratio of product 1, potassium carbonate and sulfoxide in mixture (1) is 4g:0.7g:20mL; the ratio of acyl chloride and sulfoxide in mixture (2) is 15g:45mL; the ratio of mixture (1) to mixture (2) is 40mL:9mL. Step A4: In a nitrogen atmosphere, add the monomer and crosslinking agent to toluene, stir for 20 minutes, then add PP fiber (supplier: Taian Songze Composite Materials Co., Ltd.), continue stirring for another 20 minutes, seal, and then... 60 After irradiating with Co γ rays for 11 hours, the product was removed, rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified PP fiber. The ratio of toluene, monomer, crosslinking agent, and PP fiber was 450mL:40g:15g:110g, and the crosslinking agent was divinylbenzene. 60 The dose rate of Co-γ irradiation was 5 kGy / h. Example
[0013] A corrosion-resistant refractory material comprises the following raw materials in parts by weight: 70 parts of bauxite clinker, 15 parts of metakaolin, 10 parts of aluminum ash, 10 parts of corundum, 5 parts of phenolic resin, and 12 parts of modified PP fiber; the fineness of the metakaolin is 400 mesh, and the fineness of the corundum is 400 mesh micro powder. The corrosion-resistant refractory material is prepared by the following steps: bauxite clinker (supplier: Lingshou County Chengyang Mining Co., Ltd., aluminum content 50-80%), metakaolin (supplier: Lingshou County Rongyu Mineral Products Co., Ltd.), aluminum ash (supplier: Zhengzhou Yaojuxiang Industry and Trade Co., Ltd., Al2O3 content 30-40%), corundum (supplier: Henan Taoang Industry Co., Ltd.), phenolic resin (supplier: Shandong Haoyao New Materials Co., Ltd., ash content 0.3%) and the modified PP fiber obtained in Example 1 are mixed and stirred for 1 hour, aged for 12 hours, pressed into shape at 20 MPa, dried at 200℃ for 4 hours, and then sintered at 1300℃ for 15 hours to obtain the corrosion-resistant refractory material. Example
[0014] A corrosion-resistant refractory material comprises the following raw materials in parts by weight: 75 parts of bauxite clinker, 20 parts of metakaolin, 13 parts of aluminum ash, 11 parts of corundum, 6 parts of phenolic resin, and 13 parts of modified PP fiber; the fineness of the metakaolin is 600 mesh, and the fineness of the corundum is 600 mesh micro powder. The corrosion-resistant refractory material is prepared by the following steps: bauxite clinker (supplier: Lingshou County Chengyang Mining Co., Ltd., aluminum content 50-80%), metakaolin (supplier: Lingshou County Rongyu Mineral Products Co., Ltd.), aluminum ash (supplier: Zhengzhou Yaojuxiang Industry and Trade Co., Ltd., Al2O3 content 30-40%), corundum (supplier: Henan Taoang Industry Co., Ltd.), phenolic resin (supplier: Shandong Haoyao New Materials Co., Ltd., ash content 0.3%) and the modified PP fiber obtained in Example 2 are mixed and stirred for 1.3 hours, aged for 12 hours, pressed into shape at 20 MPa, dried at 250°C for 4.5 hours, and then sintered at 1400°C for 15.5 hours to obtain the corrosion-resistant refractory material. Example
[0015] A corrosion-resistant refractory material comprises the following raw materials in parts by weight: 80 parts of bauxite clinker, 25 parts of metakaolin, 15 parts of aluminum ash, 12 parts of corundum, 7 parts of phenolic resin, and 14 parts of modified PP fiber; the fineness of the metakaolin is 800 mesh, and the fineness of the corundum is 800 mesh micro powder. The corrosion-resistant refractory material is prepared by the following steps: bauxite clinker (supplier: Lingshou County Chengyang Mining Co., Ltd., aluminum content 50-80%), metakaolin (supplier: Lingshou County Rongyu Mineral Products Co., Ltd.), aluminum ash (supplier: Zhengzhou Yaojuxiang Industry and Trade Co., Ltd., Al2O3 content 30-40%), corundum (supplier: Henan Taoang Industry Co., Ltd.), phenolic resin (supplier: Shandong Haoyao New Materials Co., Ltd., ash content 0.3%) and the modified PP fiber obtained in Example 3 are mixed and stirred for 1.5 hours, aged for 12 hours, pressed into shape at 20 MPa, dried at 300℃ for 5 hours, and then sintered at 1500℃ for 16 hours to obtain the corrosion-resistant refractory material.
[0016] Comparative Example 1 Compared with Example 6, the 2-mercaptobenzimidazole-5-sulfonate sodium dihydrate in the modified PP fiber preparation process was replaced with 2-mercaptobenzimidazole, and the rest was exactly the same as in Example 6, to obtain the refractory material.
[0017] Comparative Example 2 Compared with Example 6, the 2-mercaptobenzimidazole-5-sulfonate sodium dihydrate in the modified PP fiber preparation process was replaced with 2-methoxybenzylthiophenol, and the rest was exactly the same as in Example 6, to obtain the refractory material.
[0018] Comparative Example 3 Compared with Example 6, the pyrophyllite powder in the modified PP fiber preparation process was replaced with nano-alumina, and the rest was exactly the same as in Example 6, to obtain the refractory material.
[0019] Comparative Example 4 Compared with Example 6, the modified PP fiber was replaced with PP fiber, and the rest was exactly the same as in Example 6, to obtain a refractory material.
[0020] The refractory material prepared according to the present invention was further tested, and the test results are as follows.
[0021] Corrosion resistance test: The obtained refractory material was subjected to a static crucible slag resistance test (2500℃), and the erosion index was recorded in Table 1 to evaluate the corrosion resistance; Refractoriness test: The refractoriness of the obtained refractory materials was tested using the cone method, and the refractoriness was recorded in Table 1; Compressive strength: The room temperature compressive strength of refractory materials was determined by the tensile method in accordance with GB / T5072-2023, and the results are recorded in Table 1.
[0022] According to the data in Table 1, the refractory material of the present invention exhibits excellent corrosion resistance, compressive strength, and refractoriness. Comparing Example 6 with Comparative Example 1, it is evident that sodium sulfonate was not introduced during the preparation of the modified PP fiber. This not only fails to enhance the compatibility of the modified PP fiber with other raw materials, leading to a decrease in compressive strength, but also fails to produce a synergistic flame-retardant effect with a large amount of nitrogen, which is detrimental to improving the flame retardancy of the modified PP fiber, thus resulting in a decrease in the refractoriness of the refractory material. Comparing Example 6 with Comparative Example 2, it is evident that sodium sulfonate and benzimidazole were not introduced during the preparation of the modified PP fiber. This not only fails to impart flame retardancy to the PP fiber, but also fails to introduce a partial polybenzimidazole structure to improve the high-temperature resistance of the modified PP fiber, resulting in a significant decrease in the refractoriness of the refractory material. Furthermore, it fails to enhance the compatibility of the modified PP fiber with other raw materials, leading to a decrease in compressive strength. Comparing Example 6 with Comparative Example 3, it is evident that using nano-alumina instead of pyrophyllite powder weakens the improvement in the slag erosion resistance of the refractory material, thereby weakening its corrosion resistance. Comparing Example 6 with Comparative Example 4, it can be seen that when ordinary PP fibers are used instead of modified PP fibers, the high temperature resistance and flame retardancy of the PP fibers are poor, and the refractoriness of the resulting refractory material decreases. Furthermore, since nano-sized pyrophyllite is not introduced, the corrosion resistance and compressive strength of the resulting refractory material both decrease.
[0023] The above content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined by the present invention, and all such modifications and additions should fall within the protection scope of the present invention.
Claims
1. A corrosion-resistant and refractory material, characterized in that: The raw materials include the following parts by weight: 70-80 parts of bauxite clinker, 15-25 parts of metakaolin, 10-15 parts of aluminum ash, 10-12 parts of corundum, 5-7 parts of phenolic resin, and 12-14 parts of modified PP fiber. The modified PP fiber is prepared by the following steps: Step A1: Mix silane coupling agent and ethanol to obtain solution (1); grind pyrophyllite, measure particle size, and keep warm in an oven to obtain pyrophyllite powder. Take out the pyrophyllite powder and add anhydrous ethanol and solution (1) and stir to obtain modified pyrophyllite. Step A2: Modified pyrophyllite, sodium dihydrate of 2-mercaptobenzimidazole-5-sulfonate, DMF, and 4-dimethylaminopyridine were stirred under ultraviolet light to obtain product 1; Step A3: Add 5-hexenoic acid to DMF, add sulfoxide under stirring, and stir to obtain acyl chloride; mix product 1, potassium carbonate and sulfoxide to obtain a mixture (1), then add acyl chloride to sulfoxide and stir to obtain a mixture (2); add mixture (2) dropwise to mixture (1) and stir to obtain a monomer; Step A4: In a protective gas atmosphere, add the monomer and crosslinking agent to toluene, add PP fiber, stir, seal, and then... 60 Modified PP fibers were obtained after Co-γ ray irradiation.
2. The corrosion-resistant and refractory material according to claim 1, characterized in that: The fineness of metakaolin is 400-800 mesh, and corundum is 400-800 mesh micro powder.
3. The corrosion-resistant and refractory material according to claim 1, characterized in that: In step A1, the silane coupling agent is 5-hexenyltriethoxysilane, the volume fraction of ethanol is 95%, and the ratio of silane coupling agent to ethanol is 0.8-1.5g:20-23mL.
4. The corrosion-resistant and refractory material according to claim 1, characterized in that: In step A1, after grinding pyrophyllite, the average particle size was measured to be 900-950nm using a particle size analyzer. The ratio of pyrophyllite powder, anhydrous ethanol, and solution (1) was 50-52g: 110-120mL: 25-27mL.
5. The corrosion-resistant and refractory material according to claim 1, characterized in that: In step A2, the ratio of modified pyrophyllite, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, DMF, and 4-dimethylaminopyridine is 6-8g:0.13-0.17g:30-40mL:0.02-0.03g, the power of the ultraviolet light is 100-150W, the wavelength is 365nm, and the irradiation distance is 18-20cm.
6. The corrosion-resistant and refractory material according to claim 1, characterized in that: In step A3, the ratio of 5-hexenoic acid, DMF, and thionyl chloride is 12-13g: 90-100mL: 18-20g.
7. The corrosion-resistant and refractory material according to claim 1, characterized in that: In step A3, the ratio of product 1, potassium carbonate and dimethyl sulfoxide in the mixture (1) is 3-4g: 0.6-0.7g: 15-20mL.
8. The corrosion-resistant and refractory material according to claim 1, characterized in that: In step A3, the ratio of acyl chloride to dimethyl sulfoxide in the mixture (2) is 14-15g: 35-45mL; the ratio of mixture (1) to mixture (2) is 30-40mL: 7-9mL.
9. The corrosion-resistant and refractory material according to claim 1, characterized in that: In step A4, the ratio of toluene, monomer, crosslinking agent, and PP fiber is 400-450mL: 38-40g: 13-15g: 108-110g, and the crosslinking agent is divinylbenzene.
10. A method for preparing the corrosion-resistant and refractory material according to any one of claims 1-9, characterized in that: Includes the following steps: Bauxite clinker, metakaolin, aluminum ash, corundum, phenolic resin and modified PP fiber are mixed and stirred for 1-1.5 hours, aged, pressed into shape, dried at 200-300℃ for 4-5 hours, and then sintered at 1300-1600℃ for 15-16 hours to obtain corrosion-resistant refractory material.
